When the Bible becomes weaponized: Detecting and disarming Jew-hatred. - Levine, Amy-Jill (Studia Theologica, 2021)
Christian preaching and teaching often presents Jews and Judaism as legalistic, obsessed with ritual purity, elitist, money-loving, militaristic, misogynist, and xenophobic. In much popular Christian imagination, Jesus emerges as the only Jew who proclaims the spirit over the letter of the Law, who finds the heart of Torah in compassion rather than in ritual, who demonstrates solidarity with the poor, who counsels peace, who shows respect for women, and who proclaims that God loves all people and not just Jews. Such caricatures of both Jesus and his context are not simply the purview of neo-Nazis and their ilk; they appear in the sermons and teachings of well-motivated Christians who would be appalled to think of themselves as purveying tropes that can inculcate or reinforce Jew-hatred. The problem with such bigoted views can often be traced to biblical passages: Matthew's invectives against scribes and Pharisees, John's "Jews" who are children of the devil, Paul's reference to the Jews "who killed the Lord Jesus," the "synagogue of Satan" in Revelation, etc. This paper briefly notes ongoing Jew-hatred, explains why Christian teachers and clergy are ill-equipped to address it, details why major approaches to problematic texts are not, and cannot be, fully successful, and then suggests ways for Christian preaching and teaching to move forward in preventing anti-Jewish messages.